e-competences: new learner skills for developing knowledge in the era of education and globalization - Villanueva Flores, Gerardo; Instituto Tecnológico de Monterrey (Pontificia Universidad Javeriana - Facultad de Comunicación y Lenguaje, 2010)
This work analyzes the competences both students and future professionals require. It also studies technology-related skills needed by individuals to work within a competitive and changing context. This gives rise to the concept of e-competences or technology-related competences: a number of skills Young people and future professionals need in order to respond to demands by a competitive environment in a globalized world. Some of them are self-learning, distance contact, and social networks. This work concludes with a reflection about the competences required in the 21st Century, about the role of the education sector in the development of such competences, and about the challenges for the analysis of global phenomena related to learning and academic performance.